Pharmacists’ Ability in Recognising and Managing Angiotensin Converting Enzyme Inhibitor (ACEI)-Induced Cough in Self-Medicating Patients - Brata, Cecilia; Wibowo, Yosi Irawati; Setiawan, Eko; Halim, Steven Victoria; Razanah, Afina; Sholikhah, Ima Mar’atus; Lailla, Putri Rohmatu; Rahmadini, Azilah; Putri, Ida Ayu Elsa Ratu Satwika; Irawati, Lyna (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2026)
Background: As ACEIs are widely used and patients with cough often self-medicate at community pharmacies, pharmacists must be able to recognise ACEI-induced cough and refer patients appropriately. However, literature on pharmacists’ ability to manage ACEI-induced cough is limited.Objectives: This study aims to describe pharmacists' ability to recognise and manage a vignette case of ACEI-induced cough in self-medicating patients.Methods: This cross-sectional study was conducted in community pharmacies across a metropolitan city in Indonesia. All pharmacies were visited and pharmacists who were available and willing to participate were interviewed by five trained data collectors. An open-ended questionnaire featuring a vignette of ACEI-induced cough was used. Pharmacists were asked to provide their recommendations for the case and explain their reasoning. Responses were analysed using content analysis, involving systematic coding and categorisation of the textual data to identify underlying patterns and themes.Results: Of 245 participating pharmacists, 189 (77%) could recognise that the cough was due to ACEI. However, only 101 of these 189 participants could provide an appropriate response (i.e., direct medical referral without recommending a product to treat the cough and/or changing or stopping the ACEI).  Conclusion: While many pharmacists may possess the necessary knowledge to recognise ACEI-induced cough in the case of a self-medicating patient, they may lack sufficient knowledge about the appropriate response of this problem. Educational intervention is needed to improve pharmacists’ knowledge and ability to manage an ACEI-induced cough case.